Journal of Orthopaedic Surgery and Research Editorial - Chan Kai-Ming; Cheng Cheng-Kung (Journal of Orthopaedic Surgery and Research, 2006)
Abstract Journal of Orthopaedic Surgery and Research is an open access, online journal that aims to expeditiously publish clinical and basic research studies related to musculoskeletal issues in different cultural communities. It provides a platform for exchanges of new clinical and scientific information in the most precise and expeditious way to achieve dissemination of information and cross-fertilization of ideas. The open access nature of this journal allows articles to be universally and freely accessible via the Internet. This ensures a rapid and efficient communication of research findings. The journal welcomes all types of articles related to musculoskeletal issues. Its timely publication and high visibility are the two most important features that make this journal different from other traditional journals in the orthopaedic field.